2023
DOI: 10.1002/aesr.202200177
|View full text |Cite
|
Sign up to set email alerts
|

Novel Reliability Method Validation for Floating Wind Turbines

Abstract: Wind turbines and associated parts are susceptible to cyclic stresses, including torque, bending, and longitudinal stress, and twisting moments. Therefore, research on the resilience of dynamic systems under such high loads is crucial for design and future risk‐free operations. The method described in this study is beneficial for multidimensional structural responses that have undergone sufficient numerical simulation or measurement. In contrast to established dependability methodologies, the unique technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The recommended method efficiently uses all the available information to precisely predict extreme values. Based on the overall effectiveness of the suggested strategy, it was found that the novel de‐convolution methodology could include environmental information and provide more accurate forecasts 36‐38,51‐56 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommended method efficiently uses all the available information to precisely predict extreme values. Based on the overall effectiveness of the suggested strategy, it was found that the novel de‐convolution methodology could include environmental information and provide more accurate forecasts 36‐38,51‐56 …”
Section: Resultsmentioning
confidence: 99%
“…Based on the overall effectiveness of the suggested strategy, it was found that the novel deconvolution methodology could include environmental information and provide more accurate forecasts. [36][37][38][51][52][53][54][55][56] Figure 3 shows the final un-scaled results of the proposed de-convolution technique in this paper, namely the "shorter" decimal log scale f X PDF tail, extrapolated by de-convolution, along with "longer" data distribution tail and modified Weibull Naess-Gaidai (NG) extrapolation. Equidistant sampling was utilized to reduce the size of the "shorter" data collection by 50 times compared to the entire "longer" simulated data set.…”
Section: Resultsmentioning
confidence: 99%
“…Using traditional engineering reliability methods to estimate structural system reliability is difficult 50,[54][55][56][57][58][59][60][61] . The latter is frequently brought on by a great deal of system freedom and random factors that regulate dynamic systems.…”
Section: Gaidai-xing Methodsmentioning
confidence: 99%
“…Patient numbers from thirteen different Chinese administrative regions were chosen as components thus constituting an example of a thirteen dimensional (13D) dynamic biological system, according to Equation (2) . 39 41 …”
Section: Use Casementioning
confidence: 99%
“…While in authors similarly used EVT to predict and detect anomalies of influenza epidemics. 41 44 China was chosen to test the methodology proposed in this study, because of its COVID-19 origin and extensive health observations and related research available online. 45 50 …”
Section: Introductionmentioning
confidence: 99%